THE CORRELATION BETWEEN STUDENTS’ SIMPLE PAST TENSE MASTERY AND THEIR ABILITY IN TRANSLATING NARRATIVE TEXT PROBLEMS FACED BY STUDENTS IN APPLYING GRAMMAR ON SPEAKING SKILL AT ABA UMI STUDENTS 2017/2018 - Ratnawati; Sulastri (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
This research was about the problems faced by students in applying grammar on speaking skill at the second semester students at ABA UMI. This research was carried to find out and analyze the types of problems encountered by students. In doing the research, the researchers used qualitative approach which involved descriptive method in it. Then, the data were collected through the questionnaire. The researchers took 23 students as the sample then gave the students test that consisted of 30 items: 25 multiple choice and 5 essays questions.There were four types of errors which were usually made by students of second semester students. They were omission, addition, misformation, and misordering. From the questionnaire finding, the results showed that based on the rate of the grammar problems faced by students percentage total error of omission is 14 on the percentage 0,60%, total error of addition is 18 on the percentage 0,78%, total error of misformation is 21 on the percentage 0,91%, and total error of misoredering 10 on the percentage 0,43%. It is followed by the problems speaking skill with mean percentage, of grammar is 64%, vocabulary 25%, and Pronunciation 11%.In conclusion, problems in the application of grammar on speaking skill is higher, it concluded that the grammar problems still become barrier that affect students speaking skill.